2010
DOI: 10.1093/brain/awq155
|View full text |Cite
|
Sign up to set email alerts
|

Melanopsin retinal ganglion cells are resistant to neurodegeneration in mitochondrial optic neuropathies

Abstract: Mitochondrial optic neuropathies, that is, Leber hereditary optic neuropathy and dominant optic atrophy, selectively affect retinal ganglion cells, causing visual loss with relatively preserved pupillary light reflex. The mammalian eye contains a light detection system based on a subset of retinal ganglion cells containing the photopigment melanopsin. These cells give origin to the retinohypothalamic tract and support the non-image-forming visual functions of the eye, which include the photoentrainment of circ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
173
2
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 163 publications
(199 citation statements)
references
References 43 publications
18
173
2
6
Order By: Relevance
“…These abnormalities appear to worsen with age. Overall, these findings are similar to those described in mitochondrial optic neuropathies such as Leber hereditary optic neuropathy and dominant optic atrophy (16,17). …”
Section: Histopathologysupporting
confidence: 86%
See 2 more Smart Citations
“…These abnormalities appear to worsen with age. Overall, these findings are similar to those described in mitochondrial optic neuropathies such as Leber hereditary optic neuropathy and dominant optic atrophy (16,17). …”
Section: Histopathologysupporting
confidence: 86%
“…Pathological studies in Leber hereditary optic neuropathy and dominant optic atrophy have shown relatively preservation of melanopsin-containing ganglion cells in spite of extensive loss of the predominantly small midget/ parvocellular P-ganglion cells (17,24). This is because melanopsin retinal ganglion cells are more resistant to mitochondrial stress and neurodegeneration (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding sleep disturbances in AD, it is of note that recent studies documented impairment of melanopsin RGCs (m-RGCs) in the retina of patients with AD. m-RGCs are a population of RGCs (1-2 % of total RGC population) involved in non-image-forming visual functions, including photoentrainment of circadian rhythms [20]. In this study, m-RGC density was significantly decreased in the AD group compared with controls, and remaining mRGCs presented impaired function, altered morphology, and amyloid deposits in and around these cells.…”
Section: Ad Pathological Changes In the Posterior Visual Pathwaymentioning
confidence: 55%
“…If the age-related losses in the S-cone IRF are attributable to changes in the ipRGCs themselves, reduced responsivity to melanopsin stimulation may also be expected in natural environments. Anatomical evidence indicates that there is a loss in ipRGCs in the elderly (39). Further study is warranted to assess possible contributions of these ganglion cells to disorders of sleep and dysfunction of circadian rhythms, which become more common with increasing age (40) and have decreased stimulation by short-wave light as the result of age-related changes in the ocular media (41).…”
Section: Discussionmentioning
confidence: 99%